Driverless futures: current non-drivers' willingness to travel in driverless vehicles. Issue 15 (13th October 2021) - Kottasz, Rita; Bennett, Roger; Vijaygopal, Rohini; Gardasz, Bettina
ABSTRACT: This study examines the willingness of a sample of 526 current UK non-drivers to travel in driverless vehicles (DVs). Road traffic is predicted to increase between 10%-40% consequent to current non-drivers taking to the road; the new market including individuals who are unable or unwilling to drive: the aged, people with physical and/or mental impairments, and those who possess phobias about driving. Behavioural Reasoning Theory is employed to explore explicit and implicit attitudes of non-drivers towards DVs. Implicit attitudes towards this 'really new' product are measured via an Affect Misattribution Procedure (AMP). Sample members completed an online questionnaire containing the AMP plus items on reasons for and against DVs, beliefs and values concerning new technologies, and covariates suggested by literature in the transport marketing field.